Current achievements to reduce deforestation in Kalimantan - Stephanie Wegscheider; Judin Purwanto; Belinda Arunarwati Margono; Sigit Nugroho; Budiharto Budiharto; Georg Buchholz; Ruandha Agung Sudirman (Faculty of Geography, Universitas Gadjah Mada, 2018)
Indonesia has developed its forest reference emission level (FREL), using a historical reference period of 1990-2012. Based on official Ministry of Environment and Forestry (MoEF) data, this paper analyses gross deforestation rates and emissions from deforestation in the five provinces of the island of Kalimantan which occurred in the time after 2012, i.e. 2013 until 2015, and puts them in relation to the average annual deforestation and emission rates of each province in the reference period. Even though the overall linear trend of deforestation and emission rates in Kalimantan from 1990 until 2015 goes down, this trend is not reflected in all of the five provinces equally. West and North Kalimantan’s rates even seem to be on the rise. The potentials to achieve emission reduction targets thus remain unequal for each province in Kalimantan Island.